Diaphragmatic hernia as a rare cause of bowel obstruction. Issue 1 (24th January 2022) - Gaspar, Daniela; Constantino, Júlio; Sá, Milene; Casimiro, Carlos
Abstract: Mechanical intestinal obstruction is a common cause of acute abdominal pain that brings patients to the emergency department. One of the main causes is adhesion in the abdomen after abdominal surgery, but rarer causes exist and are a diagnostic challenge due to the similarity of the presenting symptoms. Here, we present a case of intestinal obstruction caused by diaphragmatic hernia.